Bioactive compounds and antioxidant activity of mangaba (Bioscience Journal, 2020)
The present study aimed to assess the behavior of bioactive compounds and total antioxidant activity of two mangaba varieties (H. speciosa var. gardneri and H. speciosa var.  cuyabensis) during storage, in two ripening stages. The fruit were harvested from the Germplasm bank of the School of Agronomy, at two ripening stages: “mature green” (mature fruit picked from the tree) and “fallen” (ripe fruit collected from the ground). After collection, they were transported to the laboratory, washed under running water, immersed in chlorine solution at 100 mg L-1 for 10 minutes, left to dry and stored under ambient conditions (22±1ºC and 90±5% RH). The fruit were analyzed to determine ascorbic acid content, total extractable polyphenols, yellow flavonoids and antioxidant activity using ferric reducing antioxidant power (FRAP) and ABTS (2,2’-azino-bis-(3-ethylbenzthiazoline-6-sulfonic acid). Analyses were performed daily until the mangaba were unfit for sale, using 3 repetitions with 3 fruit each. The maximum conservation time was eight days for “mature green” and two days for “fallen" fruit. The cuyabensis variety exhibited greatest ascorbic acid content at both ripening stages, in addition to higher antioxidant activity, and was therefore found to have the best potential to be marketed as a “superfruit”.